Controlling Post-Thoracotomy Pains With Local Injection Of Bupivacaine Before Surgery: A Randomized Controlled Study (Journal of Pharmaceutical Negative Results, 2022)
Objective: Controlling thoracotomy pain prevents post-op complications, including hypoxia, atelectasis, and pneumonia by improving respiratory condition. Thus, it is highly important to introduce the best pain-control method. This study aims to assess local injection of bupivacaine before surgery as a means of thoracotomy pain control.Methods: Patients were compared in a two independent groups of 40 in a double-blind randomized clinical trial conducted between February 2014 and January 2015. After anesthesia and before incision, the intervention group received subcutaneous injection of 2 mg/kg of bupivacaine 0.5% diluted with 5cc distilled water all around the incision line. The control group received normal saline in a similar way. Pain was assessed using numerical analogue scale (NAS) at 2, 4, 8, and 24 hours after surgery, and hemodynamic monitoring was performed before anesthesia, before injection (drug or placebo), and 5 minutes after incision.Results: In the intervention group, mean (± standard deviation) pain based on NAS at 2, 4, 8, and 24 hours after surgery was 5.5±5.75, 5.5±5, 2±3.5, and 5±5.5, and in the control group, 7±4.5, 8±5.25, 6±5.5, and 5.5±4, with no significant difference between the two groups (P>0.05). The two groups were not significantly different in terms of hemodynamic signs, either (P>0.05).Conclusion: No relationship was found between injection of bupivacaine at incision site and reduced thoracotomy pain or use of morphine and diclofenac. Moreover, no improvement was observed in vital signs the first time analgesic was needed.